PERAN DINAS TENAGA KERJA TRANSMIGRASI KABUPATEN BULELENG DALAM PENEMPATAN DAN PEMBERIAN PERLINDUNGAN HUKUM TENAGA KERJA INDONESIA DI LUAR NEGERI - Rai Yuliartini, Ni Putu; Sudika Mangku, Dewa Gede (Universitas Pendidikan Ganesha, 2020)
The initial process for the placement of Indonesian workers abroad, begins with registration at the Buleleng Regency Manpower Office then proceed with the recruitment process. Recruitment is carried out after a request for sending Indonesian workers from an overseas agent has been verified by an Indonesian representative in the recipient country. In this recruitment process, counseling and selection are carried out. If it passes the selection process, it will continue with the signing of the placement agreement. In this post-placement period, the government through the Buleleng Regency Manpower Office of origin of Indonesian workers prepared an empowerment program for Indonesian workers after returning to their home regions. This program is carried out in the form of capital services for full-time Indonesian workers, providing education and entrepreneurship assistance and management of work, education and assistance for Indonesian workers' organizations, including cooperative organizations for Indonesian workers and their families, as well as welfare improvement programs for Indonesian workers and in protection efforts provided by the state, it is necessary to be clear about the legal protection in force and must be followed by every foreign national in the country. Therefore, in the process of placing Indonesian workers abroad, the state is obliged to enter into bilateral agreements with the recipient country, especially with the recipient country that does not yet have legislation that provides protection for foreign workers. In implementing the protection of Indonesian Migrant Workers Overseas, there are still many obstacles which are caused by the ineffective protection system that is in accordance with the Standard Operating Procedure (SOP), the attraction of authority between the Central Government and Provincial Governments in terms of Placement Services and Worker Protection Institutions Indonesia, the assumption that the settlement of cases experienced by migrant workers is only the responsibility of BNP2TKI and UPT P3TKI, Lack of active role of the Department of Manpower and Transmigration of the Regional Government in helping the resolution of problems experienced by migrant workers, and the non-cooperation of PPTKIS in helping the Provincial Regional Government and District / City Regional Government in resolving cases.